Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3923/pjbs.2011.449.455
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Phytochemical Study of Six Medicinal Plants used in Benin

Abstract: The ethanol extracts obtained from Psidium guajava, Flacourtia flavescens Boswellia dalzielii, Ficus exasperata, Pavetta corymbosa and Hybanthus enneaspermus, six species traditionally used in Benin to treat several infectious diseases, were evaluated for their in vitro antimicrobial activity against Staphylococcus aureus, Enteroccocus feacalis, Escherichia coli and Pseudomonas aeruginosa. The minimum inhibitory concentration of extracts was determinate using the microplate dilution method. The presence of maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…To our knowledge, there is no work on successive extracts of B. dalzielii leaves. The only study of B. dalzielii (Anago et al 2011) showed that an ethanolic extract had an inhibition percentage of 83% at 10 mg/L.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…To our knowledge, there is no work on successive extracts of B. dalzielii leaves. The only study of B. dalzielii (Anago et al 2011) showed that an ethanolic extract had an inhibition percentage of 83% at 10 mg/L.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The inclusion of these plants amongst others used for malaria treatment is not unconnected with the antioxidative stress exhibited by the plants, which is directly linked with antioxidant potential of several phytochemicals of the plants species [4,7,12,[25][26][27][28] . Previous studies have shown that the plants was multipurpose species in African folk medicine in the treatment of several diseases conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Their study reported that 89 plant-derived drugs currently used in modern medicine were originally discovered by the study of traditional remedies and folk knowledge of indigenous people. Several studies reported that medicinal plants used in various localities possess antimicrobial activity and hence justify their use by the communities (Cheruiyot et al, 2009;Anago et al, 2011;Njume et al, 2011). Acalypha ornata (botanical family Euphorbiaceae) is used as an ornamental garden plant.…”
Section: Introductionmentioning
confidence: 99%